EL OCASO DE LAS NACIONES-ESTADO CASOS Y HECHOS - Begazo Villanueva, José (2008)
We are children of the past century and the last millennium, we were suckled in an Industrial Company, with its own anxieties and paradigms, and the same organizations and Institutions. Today we unfold in a Knowledge Society, where the value resides in other concepts, other attitudes and also in other referring configurations to the concept of Nation and State.